Statistical review of animal trials—A guideline. Issue 2 (7th September 2022) - Piper, Sophie K.; Zocholl, Dario; Toelch, Ulf; Roehle, Robert; Stroux, Andrea; Hoessler, Johanna; Zinke, Anne; Konietschke, Frank
Abstract: Any experiment involving living organisms requires justification of the need and moral defensibleness of the study. Statistical planning, design, and sample size calculation of the experiment are no less important review criteria than general medical and ethical points to consider. Errors made in the statistical planning and data evaluation phase can have severe consequences on both results and conclusions. They might proliferate and thus impact future trials—an unintended outcome of fundamental research with profound ethical consequences. Unified statistical standards are currently missing for animal review boards in Germany. In order to accompany, we developed a biometric form to be filled and handed in with the proposal at the concerned local authority on animal welfare. It addresses relevant points to consider for biostatistical planning of animal experiments and can help both the applicants and the reviewers in overseeing the entire experiment(s) planned. Furthermore, the form might also aid in meeting the current standards set by the 3+3R's principle of animal experimentation: Replacement, Reduction, Refinement as well as Robustness, Registration, and Reporting. The form has already been in use by the concerned local authority of animal welfare in Berlin, Germany. In addition, we provide reference to our user guide giving more detailed explanation and examples for each section of the biometric form. Unifying the set of biostatistical aspects will help both the applicants and the reviewers to equal standards and increase quality of preclinical research projects, also for translational, multicenter, or international studies.